Bridging Ideas: How Mind Mapping Enhances Dialogic Collaborative Learning Outcomes - Nor, Hidayah; Sarita, Erma; Rahayu, Puji Sri (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
Mind Mapping has gained recognition as a visual learning strategy that enhances comprehension and engagement. Yet, its application in dialogic collaborative learning within English Language Education remains underexplored. This study explores students’ perceptions of Mind Mapping as a collaborative learning tool, highlighting its pedagogical potential and challenges in higher education. Conducted at Antasari State Islamic University Banjarmasin, the research involved six English Language Education students from the 2022 cohort. Data were gathered through in-depth semi-structured interviews and analyzed using Miles and Huberman’s Interactive Model to identify key themes. Findings reveal that students view Mind Mapping as a productive tool that simplifies complex material, promotes dialogic interaction, and fosters creativity and critical thinking through deeper content engagement. However, three main challenges emerged: (1) differing preferences for digital versus manual mapping, (2) unequal participation among group members, and (3) excessive focus on visual aesthetics over content depth. The study concludes that effective integration of Mind Mapping in collaborative learning requires teacher facilitation, explicit guidance, and a balanced emphasis on both form and meaning. These insights contribute to research on collaborative learning in English Language Education and offer practical implications for educators seeking to incorporate visual tools in EFL contexts.